2017
DOI: 10.1371/journal.pone.0183788
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer motivators for participating in HIV vaccine clinical trials in Nairobi, Kenya

Abstract: Background1.5 million Kenyans are living with HIV/AIDS as per 2015 estimates. Though there is a notable decline in new HIV infections, continued effort is still needed to develop an efficacious, accessible and affordable HIV vaccine. HIV vaccine clinical trials bear risks, hence a need to understand volunteer motivators for enrolment, retention and follow-up. Understanding the factors that motivate volunteers to participate in a clinical trial can help to strategize, refine targeting and thus increase enrolmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…Altruism was the most frequently reported positive social motivator for WTP in our study, and much of the same results were reported in other studies [32,35,36], suggesting that study participation may be seen by participants as their contribution to the fight against HIV. Important to highlight, was the increase in the proportion of negative social motives.…”
Section: Plos Onesupporting
confidence: 90%
“…Altruism was the most frequently reported positive social motivator for WTP in our study, and much of the same results were reported in other studies [32,35,36], suggesting that study participation may be seen by participants as their contribution to the fight against HIV. Important to highlight, was the increase in the proportion of negative social motives.…”
Section: Plos Onesupporting
confidence: 90%
“…High education levels have been found to be associated with decreased willingness to participate in vaccine research elsewhere [ 37 ]. Participants with high levels of education are less likely to be motivated by non-altruistic reasons [ 38 ], a factor that may contribute to the relatively high level of unwillingness to participate in this sub-population. A high level of education may also be associated with having more knowledge about clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…We also learnt that participants join the study for exterior motives such as to bene t humanity or in the words of the participants, to be part of the world's efforts to ght the HIV epidemic and protect future generations. A similar study in Kenya found that one-fth of their participants were motivated by the need to nd a vaccine for future generations (31). It is commendable that participants join trials for the bene t of others and not themselves.…”
Section: Discussionmentioning
confidence: 99%
“…While on average it takes at 10.7 years to develop a vaccine from preclinical phase to market registration, it is now decades before a vaccine is found for HIV pandemic (4). Previous trials such as one conducted in Thailand which found 31.2% e cacy brought with them promises for an effective vaccine although more work is still needed (5). While there are challenges in nding a vaccine, research has documented social implications and willingness to participate in HIV vaccine trials including knowledge about vaccine, hesitance, fear of side effects, perceived risks and bene ts of participation, was social factors have often been mentioned as key socio-challenges in the development of vaccines (6)(7)(8).…”
Section: Hiv Pandemic and Vaccine Developmentmentioning
confidence: 99%